EVALUASI KELAS KEMAMPUAN LAHAN PADA KEBUN PRAKTEK FAKULTAS PERTANIAN UNIVERSITAS NUSA NIPA MAUMERE - Julianus Jeksen; Oktaviana Rosario Sere Gili (Agriculture - Jurnal Ilmu Pertanian, 2023)
The practical garden of the Faculty of Agriculture, Nusa Nipa University Maumere is a practical location for students of the Faculty of Agriculture intended for the cultivation of food crops and horticulture. The cultivation of these two types of crops at this location has been carried out intensively for several planting seasons without considering the land capability class of the land. Intensive agricultural activities on this land will continuously impact land capability, namely the degradation of land fertility, which will further affect the decrease in productivity. This research was conducted at the Practical Garden of the Faculty of Agriculture, Nusa Nipa University Maumere. The method used in this research is the survey method with data sampling using purposive sampling. Data processing was carried out using the arithmetic matching method, which involves matching the results of laboratory and field observations with the most dominant limiting factors in each sample. Based on the results of the land capability analysis using the arithmetic matching method, which is based on the most dominant land capability class from all observation parameters, the Faculty of Agriculture, Nusa Nipa University Maumere, as a whole has the same land capability class, namely Class I, with varying limiting factors, so the practical garden of the Faculty of Agriculture, Nusa Nipa University Maumere, is very suitable for agricultural cultivation activities.